FORCED OSCILLATION FOR A CLASS OF FRACTIONAL PARABOLIC PARTIAL DIFFERENTIAL EQUATIONS (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
We investigate the oscillation of class of time fractional partial dierential equationof the formfor (x; t) 2 R+ = G; R+ = [0;1); where is a bounded domain in RN with a piecewisesmooth boundary @ ; 2 (0; 1) is a constant, D +;t is the Riemann-Liouville fractional derivativeof order of u with respect to t and is the Laplacian operator in the Euclidean N- space RNsubject to the Neumann boundary conditionWe will obtain sucient conditions for the oscillation of class of fractional partial dierentialequations by utilizing generalized Riccatti transformation technique and the integral averagingmethod. We illustrate the main results through examples.